Spontaneously restored electrical conductivity of bioactive gel comprising mussel adhesive protein-coated carbon nanotubes. Issue 90 (13th September 2016) - Lee, Hyunjung; Ha, Yu-Mi; Lee, Sang Hyun; Ko, Young-il; Muramatsu, Hiroyuki; Kim, Yoong Ahm; Park, Min; Jung, Yong Chae
Abstract : We demonstrated the pH-mediated self-healing performance of an electrically conductive gel comprising mussel adhesive proteins (MAPs) and carbon nanotubes (CNTs). Abstract : We demonstrated the pH-mediated self-healing performance of an electrically conductive gel comprising mussel adhesive proteins (MAPs) and carbon nanotubes (CNTs). We observed that optically strong and electrically conductive CNTs are dispersed stably in an aqueous solution with a homogeneous coating of MAPs and they are agglomerated reversibly via a sol–gel phase transition. The formation of the coordination bonding between MAPs and metal ions upon pH change was confirmed based on the optical studies of the inner tubes of the DWNTs. The hybrid gel with relatively good electrical conductivity (1.5 × 10 −3 S m −1 ) exhibited self-repaired electrical conductivity under repetitive mechanical cutting. The material prepared in this work is potentially useful in wearable electronics and biosensors as well as in medical adhesives, where electrical conductivity, a self-healing ability and good biocompatibility are simultaneously required.